GOOD WISHES AS A MAGICAL GENRE OF LEZGHIN FOLKLORE (Proceedings of Southern Federal University. Philology, 2024)
DOI 10.18522/1995-0640-2024-4-165-173The article is devoted to one of the least studied problems in Lezghin folklore – the magical genre of oral and poetic creativity. We find elements of the magical genre in the structure of good wishes, curses, conspiracies, ritual and mythological works. We touch upon the texts of magical poetry (good wishes), which were first introduced into scientific circulation. Along with other genres of folklore, Lezghins present good wishes. It has been established that good wishes are one of the very archaic genres of folk art. The ideological and thematic orientation of the works of this genre is directly related to the wishes of all kinds of benefits for any significant occasion in life. Good wishes were associated with different situations and life circumstances – from birth to death. A specific feature of good wishes is their connection with various rituals. These rituals are closely related to incantatory verbal formulas and the corresponding ritual songs. It has been proven that good wishes are an organic part of wedding ritual songs, calendar ritual songs and spells. The good wishes in the article are analyzed on specific national material. Good wishes can be expressed in both poetic and prose form. We have conditionally divided the texts into several thematic groups.Key words: Lezghin folklore, magic genre, good wishes, ritualism